Weaving Through Fire and Force: Fire Behavior and Fire Stability of Unidirectional, Bidirectional, and Woven Roving Glass‐Fiber Composites - Maria Jauregui Rozo; Sruthi Sunder; Sneha Inasu; Dietmar Meinel; Holger Ruckdäschel; Bernhard Schartel (Macromolecular Materials and Engineering)
Abstract This study systematically investigates the transfer of flame retardants (FRs) from epoxy resins to composites. The flame‐retardant composites are formulated using bisphenol A diglycidyl ether as the resin and dicyandiamide as the hardener, reinforced with glass fibers (GFs) using various textile architectures: unidirectional (UD), bidirectional (BD), and woven rovings (WR). These composites are evaluated using bench‐scale fire stability tests and cone calorimeter experiments to assess critical parameters, including the temperature at failure, time to failure, and fire behavior. Among the tested configurations, UD‐GFs demonstrate superior flame retardancy, fire stability, flammability, and mechanical performance, attributed to their higher residue yield, forming a more efficient protective char layer. However, the addition of FRs is limited by their impact on the material's mechanical properties. When the FR content increases to 30 and 50 wt.% of the resin, the composites exhibit a decrease in mechanical performance, adversely affecting both time to failure and temperature at failure. While adding FRs reduces the risk of fire propagation, it does not substantially enhance fire stability or mechanical performance.